Isolated inguinal lymph node metastasis in early stage testicular seminoma: a case report and review of the literature - Aytekin, Aydin; Sahin, Suleyman; Hacioglu, Muhammet Bekir; Karatas, Fatih; Gurcay, Nesrin; Altinbas, Mustafa (European Journal of Oncology and Environmental Health, 2016)
Inguinal lymph node metastasis in patients with testicular seminoma is exceptionally infrequent. We here present a case of early stage (stage 1A) testicular seminoma developing inguinal lymph node metastasis without involvement of the epididymis or tunica vaginalis according to a biopsy specimen. A 31 year-old male patient presented with a left testicular mass. Post-orchiectomy biopsy materials revealed a classical type of seminoma with clear surgical margins. The primary tumor was limited to the testicle without involvement of the epididymis or tunica vaginalis (pT1). Following surgery, clinical staging was compatible with stage 1A seminoma and close surveillance without any further treatment was planned by way of management. However, the patient came back with inguinal lymph node metastasis 5 months after surgery. We report this case as an important and conflicting clinical issue that requires to be elucidated since lymph node metastasis in an early stage of testicular seminoma is unexpected.